2020
DOI: 10.3390/lubricants8050054
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between the Action of Nano-Oxides and Conventional EP Additives in Boundary Lubrication

Abstract: Additives are essential in lubricant development, improving their performance by the formation of a protective film, thus reducing friction and wear. Some such additives are extreme pressure additives. However, due to environmental issues, their use has been questioned because their composition includes sulfur, chlorine, and phosphorus. Nanoparticles have been demonstrated to be a suitable substitute for those additives. This paper aims to make a comparison of the tribological performance of conventional EP ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…This deposition can compensate for the mass loss on the contact surfaces by the "mending effect". This mechanism of CuO nanoparticles was reported in previous research, where CuO nanoparticles were used as an additive in synthesis oil [25].…”
Section: Tribofilm Thicknesssupporting
confidence: 79%
See 2 more Smart Citations
“…This deposition can compensate for the mass loss on the contact surfaces by the "mending effect". This mechanism of CuO nanoparticles was reported in previous research, where CuO nanoparticles were used as an additive in synthesis oil [25].…”
Section: Tribofilm Thicknesssupporting
confidence: 79%
“…Similar to CuO, ZnO nanoparticles have been used as additives for improving the tribological behavior in many types of lubricating oils [ 22 , 23 , 24 , 25 , 26 ]. Mana et al [ 22 ] reported that the addition of ZnO nanoparticles in mineral-based oil showed better friction reduction ability than the commonly used anti-wear additives ZDDP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plenty of nanomaterials have been used for this objective. This includes carbon and its derivatives (Gr [26], MWCNT [27], ND [28,29]), oxides of inorganic compounds (ZnO [30,31], CuO [32] MgO [33], TiO 2 [34]), and transition metal dichalcogenide (MoS 2 [35]).…”
Section: Basic Conceptsmentioning
confidence: 99%
“…A recent study was conducted with CuO and ZnO with a concentration of 0.5 wt.% compared with the commonly used anti-wear additive ZDDP [10]. Both of the nanoparticles showed a considerable tribological enhancement regarding friction reduction and antiwear behavior.…”
Section: Introductionmentioning
confidence: 99%